Questions concerning religious conceptions and church customs - Lund University Church History Archive, Lund University (Lund University, 2014)
When this study began in the 1940s the researchers set out with the view that a formerly more or less universal Swedish unitary ecclesiastic culture was in the process of dissolving. The socio-economic changes of the early 19th century were believed to have led to religious conceptions differentiating and customs not being taken for granted any more. The scientists held that only small parts remained of an earlier natural and unitary ecclesiastic culture.
Based on this view the researchers conducted an extensive project to gather information about those remains of this earlier church life that were still to be found, in the same way that general ethnography conducted research on customs in other areas of life. The researchers were of the opinion that earlier research had ignored the spiritual side of folk life and that this was problematic since it missed an important part of the daily life and ways of thinking of the population that were deeply rooted in Christianity.

Purpose:

To document those ecclesiastic customs and practices which at the time when the study was conducted were considered to be the dwindling left-overs of a former "ecclesiastic unitary culture".

About 5.600 text files containing free-text answers to the questions of the study from respondents from all parts of Sweden. The files are sorted according to diocese and parish. Also included is an accessions register in spreadsheet format. NOTE! The text files are encoded as UTF-8. If the Swedish characters å, ä and ö are not displayed properly you need to change the program's settings to UTF-8.

När denna studie började genomföras på 1940-talet utgick forskarna från uppfattningen att en kyrklig enhetskultur som tidigare varit mer eller mindre enarådande i Sverige var på väg att lösas upp. Det tidiga 1800-talets socioekonomiska förändringar antogs ha lett till att de religiösa föreställningarna differentierats och seder och bruk blivit mindre självklara. Man menade att bara rester återstod av en tidigare självklar och enhetlig kyrklig kultur.
Med utgångspunkt i denna föreställning utförde forskarna ett omfattande projekt för att samla in uppgifter om de rester av detta tidigare kyrkoliv som ännu fanns kvar, på samma sätt som den allmänna folklivsforskningen utforskade seder och bruk inom andra livsområden. Man menade att den andliga sidan av folklivet förbisetts i tidigare forskning och att detta var problematiskt eftersom man då missade en viktig del av befolkningens vardagsliv och tankesätt som var djupt förankrade i kristendomen.

Syfte:

Att dokumentera de kyrkliga seder och bruk som vid studiens genomförande uppfattades som försvinnande rester av en tidigare "kyrklig enhetskultur".

Ca 5 600 textfiler med svar i fritext på studiens frågor från respondenter i hela Sverige. Filerna är ordnade efter stift och socken. I setet ingår också en accessionskatalog i Excel-format.OBS! Notera att textfilerna är kodade i UTF-8. Om å, ä och ö visas som andra tecken behöver du byta programmets teckenkodning till UTF-8.
Frågor angående religiösa föreställningar och kyrklig sed
Keywords: religion; religion; ethics; etik; church; kyrka; religious practice; religionsutövning; history; historia; ethnography; etnografi; folk cultures; folkkulturer; folklore; folksagor; religious behaviour; religiöst beteende; pastoral work; själavårdande arbete; religious ceremonies; religiösa ceremonier; religious doctrines; religiös doktrin; cultural history; kulturhistoria; religious institutions; religiösa institutioner; religious buildings; byggnader för religionsutövning; social history; socialhistoria; funerals; begravningar; modern history; modern historia; 19th century; 1800-tal; 20th century; 1900-tal; Higher and further education; Gymnasial och högre utbildning; Religion and values; Religion och värderingar; HISTORY; HISTORIA; History; Historia; Religious Studies; Religionsvetenskap; History of Religions; Religionshistoria; Ethnology; Etnologi; Music; Musik